Analysis of Selected Forestry Indicators in Hungary and Slovakia from European Area - KOREČKO, Jaroslav; SUHÁNYIOVÁ, Alžbeta (Journal of Environmental Management and Tourism, 2017)
In this paper we would like to examine similarity respectively the diversity of selected economic and other aspects of Slovak and Hungarian forestry. We have analyzed the structure of ownership in forestry, species composition of forests, timber trade, employment in forestry sectors, international timber trade and other significant indicators. Than we have focused on several forestry indicators within the whole European Union. We have used them as the input data for cluster analysis to verify assumption of similarity in the examined group of states. We have used hierarchical and also non-hierarchical methods of clustering. Main objective of the paper is to explore several indicators of Hungarian and Slovak forestry, compare them, try to identify issues and formulate some proposals for forestry in the future.